ETHICAL ISSUES IN CONDUCTING A RESEARCH: GUIDANCE FOR NOVICE RESEARCHERS - Meliana Damayanti; Noor Shakira Aliana Binti Alias; Nur Zafira Binti Hazli; Sharija Bt Che Shaari; Yusnita Binti Mohd Yusof (Journal of Islamic, Social, Economics and Development, 2017)
The paper aims to provide some guidance to the novice researchers pertaining to the ethical issues that they might encounter in conducting a research. This paper discusses the stages where ethical issues may arise. This paper reviews these stages and discusses how they may relate to a research process. Ethical principles can be used to guide a research in addressing the issues arising from the research in order to meet the objective of the research as well as to maintain the rights of the research participants. The sources for the data are derived from published papers, key texts, reports and policy documents that relate to the methodological and ethical issues in conducting qualitative research. This paper will contribute to the existing knowledge. It will also guide the novice researchers as what they should know prior to commencing a research, while the research is on-going and presenting the research findings ethically. It is the obligation of the researchers to protect both the rights and welfare of the research participants